Performance improvement programs may help reduce the surgical backlog in South African hospitals - Ramesar, Shamal V. (International Surgery Journal, 2021)
The COVID-19 pandemic has presented an unprecedented dilemma to healthcare systems around the world, leaving many countries with the burden of massive surgical backlogs, caused by the postponement or cancellation of elective surgical procedures. Current ideas to reduce the consequential impact of this surgical backlog on patient morbidity and mortality is to increase surgical volumes, however in under-resourced countries such as South Africa this idea may be more difficult to implement due to a shortage of facilities and clinical staff. In addition, the current infrastructure, especially those in many public healthcare facilities are poor and this coupled with limited financial resources presents further challenges. Also, all hospitals both public and private alike, cannot function at full capacity due to COVID-19 protocols. Given these limitations, performance improvement strategies must be implemented with some urgency in order to limit further backlogs and disruptions to surgical outputs. Evidence-based, best practice strategies such as surgical bundles, care pathways and enhanced recovery after surgery programs have been shown to improve surgical outcomes and reduce hospital stay. Since the bottleneck to surgical volume lies in post-operative care and not theatre capacity, implementation of such programs may help to improve patient throughput, thereby increasing surgical volumes and could possibly be the answer towards reducing these overwhelming backlogs.